2002
DOI: 10.1053/jhep.2002.36497
|View full text |Cite
|
Sign up to set email alerts
|

Interorgan ammonia and amino acid metabolism in metabolically stable patients with cirrhosis and a TIPSS

Abstract: Ammonia is central to the pathogenesis of hepatic encephalopathy. This study was designed to determine the quantitative dynamics of ammonia metabolism in patients with cirrhosis and previous treatment with a transjugular intrahepatic portosystemic stent shunt (TIPSS). We studied 24 patients with cirrhosis who underwent TIPSS portography. Blood was sampled and blood flows were measured across portal drained viscera, leg, kidney, and liver, and arteriovenous differences across the spleen and the inferior and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
130
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 45 publications
10
130
2
9
Order By: Relevance
“…El 90% es metabolizado en el hígado dando lugar a la síntesis de urea que sufre posteriormente eliminación renal. En situación de cirrosis hepática, la contribución de otros órganos a la eliminación de amoniaco puede ser muy importante, destacando el papel del músculo esquelético, por su capacidad para la síntesis de glutamina (4). Una vez que el amoniaco atraviesa la barrera hematoencefálica es metabolizado a glutamina en el interior del astrocito, una reacción que consume mucha energía y podría conllevar estrés oxidativo y disfunción celular.…”
Section: Punto De Vistaunclassified
See 1 more Smart Citation
“…El 90% es metabolizado en el hígado dando lugar a la síntesis de urea que sufre posteriormente eliminación renal. En situación de cirrosis hepática, la contribución de otros órganos a la eliminación de amoniaco puede ser muy importante, destacando el papel del músculo esquelético, por su capacidad para la síntesis de glutamina (4). Una vez que el amoniaco atraviesa la barrera hematoencefálica es metabolizado a glutamina en el interior del astrocito, una reacción que consume mucha energía y podría conllevar estrés oxidativo y disfunción celular.…”
Section: Punto De Vistaunclassified
“…El metabolismo nitrogenado es complejo y en los últi-mos años se ha identificado un papel importante de diferentes tejidos, como el músculo esquelético y el riñón (4,40). En este sentido es importante señalar que la cirrosis hepática se acompaña de malnutrición energético-proteica.…”
Section: Medidas Dietéticasunclassified
“…Hepatic and inter-organ traffick�� ing of ammonia and its metabolite, glutamine (GLN), lead to hyperammonemic conditions. GLN metabolism via glutaminase is located in the intestinal epithelial cells and in the colonic epithelial cells [4] . Removal of hepatic ammonia is a differentiated work that includes the peri�� portal hepatocyte, through the urea cycle and the pe�� rivenous hepatocytes converting ammonia into GLN converting ammonia into GLN via glutamine synthetase.…”
Section: Introductionmentioning
confidence: 99%
“…Historically it was thought that the majority of ammonia was produced by gut bacteria, and treatment regimens including non-absorbable antibiotics and enemas have been extensively used. Contrary to popular belief, it has now been shown that at least 50-60% of total gut ammonia is derived from uptake of glutamine, which is metabolized to glutamate and ammonia by the enzyme glutaminase (GA) (Olde Damink, Jalan et al 2002;Romero-Gomez, Ramos-Guerrero et al 2004). Ammonia that would normally be converted to urea by a healthy liver increases to toxic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the enzyme glutamine synthetase (GS) plays a pivotal role in ammonia detoxification, effectively removing ammonia during the conversion of glutamate to glutamine (Rose, Michalak et al 1999). Glutamine deamidation by intestinal GA seems to be the main source of ammonia in patients with cirrhosis (Olde Damink, Jalan et al 2002), and hyperammonaemia and hepatic encephalopathy can appear without the participation of gut bacteria (Weber and Veach 1979).…”
Section: Introductionmentioning
confidence: 99%